Genome‐wide study of mRNA degradation and transcript elongation in Escherichia coli - Huiyi Chen; Katsuyuki Shiroguchi; Hao Ge; Xiaoliang Sunney Xie (Molecular Systems Biology, 2015)
Abstract An essential part of gene expression is the coordination of RNA synthesis and degradation, which occurs in the same cellular compartment in bacteria. Here, we report a genome‐wide RNA degradation study in Escherichia coli using RNA‐seq, and present evidence that the stereotypical exponential RNA decay curve obtained using initiation inhibitor, rifampicin, consists of two phases: residual RNA synthesis, a delay in the interruption of steady state that is dependent on distance relative to the mRNA's 5′ end, and the exponential decay. This gives a more accurate RNA lifetime and RNA polymerase elongation rate simultaneously genome‐wide. Transcripts typically have a single RNA decay constant along all positions, which is distinct between different operons, indicating that RNA stability is unlikely determined by local sequences. These measurements allowed us to establish a model for RNA processing involving co‐transcriptional degradation, providing quantitative description of the macromolecular coordination in gene expression in bacteria on a system‐wide level.